Internet connectivity disruption in Ghana (Ghana) - Voidly (2026)
CRITICAL severity disruption detected in Ghana. Confidence: 67%. Data sourced from IODA.
Network Disruption Incident ID: GH-2026-0054
Keywords: internet disruption; GH; disruption; critical